Apodemes associated with limbs support serial homology of claws and jaws in onychophora (velvet worms). (7th August 2013) - de, Ivo; Mayer, Georg
ABSTRACT Although the onychophoran jaw blades are believed to be derivatives of foot claws, serial homology of these structures has not been demonstrated. To shed light on the evolutionary origin of the onychophoran jaws, we searched for morphological landmarks and compared the internal and external anatomy of jaws and distal leg portions in representatives of the two major onychophoran subgroups, the Peripatidae and Peripatopsidae. Our data revealed hitherto unknown structures associated with the onychophoran limbs, such as a soft diastemal membrane separating the anterior and posterior portions of the inner jaw blade (present only in Peripatidae), apodemes associated with feet, an eversible dorsal sac at the basis of each foot claw, and a specific arrangement of musculature associated with the sclerotised claws, jaws and their apodemes. Specific correspondences in structure and position of apodemes support serial homology of claws and jaws, suggesting that the onychophoran jaw evolved from the distal portion rather than the entire limb in the last common ancestor of Onychophora. J. Morphol. 274:1180–1190, 2013. © 2013 Wiley Periodicals, Inc.